2021
DOI: 10.3390/nu13124214
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Oral Administration of Flavan-3-ols Induces Browning in Mice Adipose Tissues through Sympathetic Nerve Activation

Abstract: We previously found increases in uncoupling protein (Ucp)-1 transcription in brown adipose tissue (BAT) of mice following a single oral dose of flavan 3-ol (FL)s, a fraction of catechins and procyanidins. It was confirmed that these changes were totally reduced by co-treatment of adrenaline blockers. According to these previous results, FLs possibly activate sympathetic nervous system (SNS). In this study, we confirmed the marked increase in urinary catecholamine (CA) s projecting SNS activity following a sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Some flavones and flavone metabolites have been observed to modulate neural processes. Catechin and procyanidin flavan-3-ols are transported by nerves and effect adipose tissue mediated nerve activation [ 101 ]. The flavonoid isoliquiritigenin activates GABA B receptors, decreasing entry of Ca 2+ into rat cerebrocortical nerves through voltage-gated Ca 2+ channels, affecting glutamate transport and release from synaptic vesicles, and the transduction of neurotransmitters in neural networks [ 102 ].…”
Section: Neuroregulatory Properties Of Flavonoidsmentioning
confidence: 99%
“…Some flavones and flavone metabolites have been observed to modulate neural processes. Catechin and procyanidin flavan-3-ols are transported by nerves and effect adipose tissue mediated nerve activation [ 101 ]. The flavonoid isoliquiritigenin activates GABA B receptors, decreasing entry of Ca 2+ into rat cerebrocortical nerves through voltage-gated Ca 2+ channels, affecting glutamate transport and release from synaptic vesicles, and the transduction of neurotransmitters in neural networks [ 102 ].…”
Section: Neuroregulatory Properties Of Flavonoidsmentioning
confidence: 99%
“…Polyphenols appear to have a similar effect to GLP-1 agonists in weight loss by suppressing appetite and reducing gastric emptying [187,188]. Increased sympathetic activity after ingestion of astringent polyphenols is thought to cause fat browning, as confirmed in the study using rodents [118]. In addition, this promotion of lipid oxidation induced by the consumption of astringent polyphenols has also been shown to increase HDL cholesterol levels in the blood [189,190].…”
Section: Obesity and Polyphenolsmentioning
confidence: 86%
“…Repeated administration of the flavanol cinnamtannin A2 (A2, epicatechin tetramer) for two weeks also resulted in significant activation of the Akt/mTOR pathway and a marked increase in the mean muscle cross-sectional area in the soleus muscle [119] as similar to adrenalin agonist clenbuterol [120]. It has also been observed that after a single dose of flavanol, blood catecholamine levels were significantly increased [121] and urinary catecholamine excretion was also elevated [118]. These results confirm that FL induces sympathetic hyperactivity (Figure 2b).…”
Section: Astringency Perception Is a Stressormentioning
confidence: 99%
See 1 more Smart Citation